f(x)= |
dF(x) ---- dx |
Rad | degrees | sin | cos |
0π | 0 | 0 | 1 |
1/6π | 30 | 1/2 | 1/2 √ 3 |
1/4π | 45 | 1/√2 | 1/√2 |
1/3π | 60 | 1/2 √3 | 1/2 |
1/2π | 90 | 1 | 0 |
f(x) | = | x -------- dx (1+x^{2})^{3} |
f(x) | = | 4x^{4}+4x^{3}+x^{2}+3 ---------------- 2x+1 |
f(x) | = | 4x^{4}+4x^{3}+x^{2}+3 ---------------- 2x+1 |
= | 2x^{3}+x^{2}+x+ | 3 ---- 2x+1 |
∫f(x)dx | = | ∫ ( | 4x^{4}+4x^{3}+x^{2}+3 ---------------- 2x+1 |
) dx | = | ∫ ( | 2x^{3}+x^{2}+x+ | 3 ---- 2x+1 |
) dx |
∫f(x)dx | = | ∫ | x^{2}+3 -------- dx 2x |
∫ f(x)dx | = | ∫ | x^{2}+3 -------- dx 2x |
= | ∫ | x^{2} --- dx 2x |
+ | ∫ | 3 --- dx 2x |